OPRM1 genotype and naltrexone response in depressed alcohol-dependent patients. Issue 5 (May 2015) - Foulds, James A.; Ton, Kim; Kennedy, Martin A.; Adamson, Simon J.; Mulder, Roger T.; Sellman, J. Douglas
Abstract : A functional polymorphism rs1799971 (A118G) in the μ-opioid receptor gene ( OPRM1 ) produces an amino acid substitution Asn40Asp, which is believed to influence naltrexone response in nondepressed alcohol-dependent patients. In this study, patients with alcohol dependence and major depression ( n =108) received open-label naltrexone and clinical case management for 12 weeks, and were randomized to citalopram or placebo. General linear mixed models examined the effect of the OPRM1 A118G genotype on alcohol outcomes during treatment. There was no evidence of any difference in the percentage of days abstinent, drinks per drinking day or percentage of heavy drinking days between Asp40 carriers and noncarriers during treatment. This study therefore failed to replicate the previous positive findings for this single nucleotide polymorphism in relation to naltrexone response, possibly indicating that the effect is not present in depressed patients.